Assessment of behavioral, neuroinflammatory, and histological responses in a model of rat repetitive mild fluid percussion injury at 2 weeks post-injury - Fronczak, Katherine M.; Roberts, Andrea; Svirsky, Sarah; Parry, Madison; Holets, Erik; Henchir, Jeremy; Dixon, C. Edward; Carlson, Shaun W. (Frontiers in Neurology, 2022)
Repetitive mild traumatic brain injury (rmTBI) is a prominent public health concern, with linkage to debilitating chronic sequalae. Developing reliable and well characterized preclinical models of rmTBI is imperative in the investigation of the underlying pathophysiological mechanisms, as models can have varying parameters, affecting the overall pathology of the resulting injury. The lateral fluid percussion injury (FPI) model is a reliable method of TBI replication in rodent subjects, though it is currently underutilized in rmTBI research. In this study, we have performed a novel description of a variation of the lateral repetitive mild FPI (rmFPI) model, showing the graded acute behavioral impairment and histopathology occurring in response to one, two or four mild FPI (1.25 atm) or sham surgeries, implemented 24h apart. Beam walking performance revealed significant motor impairment in injured animals, with dysfunction increasing with additional injury. Based upon behavioral responses and histological observations, we further investigated the subacute pathophysiological outcomes of the dual FPI (dFPI). Immunoreactivity measures showed that dFPI led to no significant changes in synaptic density two weeks post-injury, as measured by synaptophysin abundance, but did lead to a striking increase in Iba-1-positive microglia in several brain regions. With this study, we have provided a novel account of the subacute post injury outcomes occurring in response to a rmFPI with these parameters, also demonstrating the reliability of the lateral FPI model in rmTBI replication.